2005
DOI: 10.1111/j.1399-3038.2005.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased IFN‐γ secretion from duodenal biopsy samples in delayed‐type cow's milk allergy

Abstract: A delayed and local gastrointestinal hypersensitivity to cow's milk (CM) protein is difficult to diagnose and there are limited data on this disorder. The aim of this study was to investigate local intestinal cytokine secretion in the upper small intestine in children with delayed-type cow's milk allergy (CMA). Duodenal biopsy samples from 31 children with delayed CMA, 14 with celiac disease (CD), and 14 healthy controls were studied for the spontaneous release of IFN-gamma, TNF-alpha, IL-2, IL-4, IL-5, and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 25 publications
1
37
0
1
Order By: Relevance
“…Our study showed that levels of IFN-γ were higher in children from the IgEindependent group than in children from the IgE-dependent group. Paajanen et al observed an increased level of IL-4, IL-5 and IFN-γ from duodenal biopsy in children with delayed cow's milk allergy when an elimination diet was not introduced [32]. The results of our study showed lower concentration of IL-2 in allergic groups (especially in children with IgE-dependent allergy).…”
Section: Discussionsupporting
confidence: 53%
“…Our study showed that levels of IFN-γ were higher in children from the IgEindependent group than in children from the IgE-dependent group. Paajanen et al observed an increased level of IL-4, IL-5 and IFN-γ from duodenal biopsy in children with delayed cow's milk allergy when an elimination diet was not introduced [32]. The results of our study showed lower concentration of IL-2 in allergic groups (especially in children with IgE-dependent allergy).…”
Section: Discussionsupporting
confidence: 53%
“…The LAR to foods has also been reported, but its immunological mechanism has not yet been sufficiently clarified [2,9,10,14,17,18,23,26,27,38]. In the DYAR to food challenge that we described previously [26,27], which is analogical to the DYAR induced by inhalant allergens [49], an involvement of the cell-mediated hypersensitivity mechanism could be presumed [13,15,16,18,19,20,21,22,23,24,26,27,49]. However, there is still a dearth of structural information concerning the immunological mechanisms underlying the particular food-induced AR types investigated in large groups of well-defined patients [1,2,3,6,7,8,17,23,25,26,27,30,37,38,39,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Food allergy was previously classically attributed to the involvement of the immediate (IgE-mediated) hypersensitivity mechanism [1,2,3,4,5,6,7,8,9,10,11,17,22,23,25,26,27,28,29,30,31,32,33,34]. However, evidence has been found for the possible involvement of other, so-called non-IgE-mediated, hypersensitivity types, such as late (immune-complex-mediated) and delayed (cell-mediated) types of hypersensitivity in food allergy [1,3,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. Food allergy can also be a factor in disorders of the respiratory tract, such as bronchial asthma [1,2,3,4,8,9,10,11,21,23,24,25,26,27,28,29,30,31,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations